4,535 UMP graduands celebrated in MKK17 starting this Saturday - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUANTAN, 5 November 2022 - A total of 4,535 graduands of Universiti Malaysia Pahang (UMP) will graduate at the 17th UMP Convocation Ceremony from 5 to 8 November 2022 at UMP Gambang Campus or now known as UMP Paya Besar.